2008
DOI: 10.1002/ibd.20315
|View full text |Cite
|
Sign up to set email alerts
|

Linking genetic susceptibility to Crohnʼs disease with Th17 cell function: IL-22 serum levels are increased in Crohnʼs disease and correlate with disease activity and IL23R genotype status

Abstract: The Th17 cytokine IL-22 is expressed at high levels in CD and correlates with disease activity, offering a better separation between active and inactive CD than IL-6 and TNF-alpha. IL23R genotypes influence IL-22 serum expression, linking genetic CD susceptibility to Th17 cell function for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
139
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(156 citation statements)
references
References 50 publications
13
139
2
1
Order By: Relevance
“…Ikeuchi et al found that IL-22 promoted the proliferation of synovial fibroblasts and increased the secretion of various inflammatory mediators and cytokines, which participate in the pathogenesis of rheumatoid arthritis (27). Schmechel et al found that IL-22 serum levels in Crohn's patients were significantly higher compared to the normal controls and closely related with disease activity (19). Wolk et al found that the expression of IL-22 was unusually high in psoriatics patients (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ikeuchi et al found that IL-22 promoted the proliferation of synovial fibroblasts and increased the secretion of various inflammatory mediators and cytokines, which participate in the pathogenesis of rheumatoid arthritis (27). Schmechel et al found that IL-22 serum levels in Crohn's patients were significantly higher compared to the normal controls and closely related with disease activity (19). Wolk et al found that the expression of IL-22 was unusually high in psoriatics patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…IL-22 is a member of the IL-10 family and is mainly expressed in activated T and natural killer cells. Its biological targets are epithelial or parenchymal cells in the gut, lungs, skin and kidneys (14)(15)(16) (17)(18)(19)(20). Previous studies have reported that in TPE and MPE, the levels of IL-22 are high (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…It is also plausible that IL-22 may display proinflammatory and/or tissue-protective effects at different phases of the inflammatory response. With increased IL-22 levels in active lesions of IBD patients, 18,19 and increased serum levels of IL-22 correlating with disease activity in Crohn disease, 56 additional research is required to establish what factors control the outcome of IL-22 signaling in the intestine. Such information will be essential to help establish whether this cytokine can be exploited for clinical benefit.…”
Section: Th17 Cytokines In H Hepaticus Colitismentioning
confidence: 99%
“…Evidence linking T H 17 responses include elevated levels of IL-17A and IL-22 in patients suffering from inflammatory bowel disease (IBD). 105,106 A recent report also demonstrated an increased susceptibility and resistance to IBD was linked to polymorphisms in the IL-23 gene locus. 107,108 In support of this, abrogation of IL-23 in mouse models of IBD greatly attenuates disease.…”
Section: T H 17 Cells In Gut Diseasesmentioning
confidence: 99%